Sequence analysis of the human DNA flanking sites of human immunodeficiency virus type 1 integration. - Stevens, S W (1996)
Human immunodeficiency virus type 1 (HIV-1) tagged with the Escherichia coli supF gene has been used to clone integrated HIV-1 proviruses. Sequence analysis of the 600 to 800 bp of human DNA adjacent to 29 clones revealed a propensity for HIV-1 to integrate near the Alu class of human repetitive elements.